Induced polyploidy deeply influences reproductive life cycles, related phytochemical features, and phytohormonal activities in blackberry species - Sabooni, Nasrin; Gharaghani, Ali (Frontiers in Plant Science, 2022)
In some cases, polyploidy is an important phenomenon in the evolution of fruit crops. Polyploidy can be used in fruit breeding programs to develop varieties with higher yield and better fruit quality, as well as better adaptation to adverse environmental conditions. In this study, three wild species of blackberry were subjected to different degrees of induced polyploidy, the effects of which were evaluated on morphological, physiological and phytohormonal traits. With the aim of gaining a deep insight into the generative phase of plant growth and development, different levels of induced polyploidy were evaluated on the three blackberry species, i.e. Rubus persicus Bioss. (2x, 4x and 8x), R. caesius L. (2x and 4x) and R. hirtus Schreb. (2x and 4x). The results showed that the polyploid plants performed significantly better than their diploid counterparts in terms of morphological traits such as flower count per spike and berry weight, as well as biochemical traits such as total soluble solids in the leaves. Induced polyploidy increased berry weight and drupe count per fruit. Microscopic examinations revealed a smaller number of viable pollen in the polyploids, compared to the diploids. Electron microscopy showed that the octaploid R. persicus had larger conical cells on the flower surface, compared to the diploid R. persicus. Correlation analysis showed that the ratio of indoleacetic acid to jasmonic acid changed synergistically with the total soluble solids in the leaves during fruit set. The ploidy level correlated significantly with the number of pistils, leaf green index, total soluble solids in the leaves, and glucose content in floral nectar. Overall, induced polyploidy allowed Rubus to develop advantageous traits that can benefit future breeding programs and expand reproductive research in blackberry.